Konstruksi Pengaturan Penyidikan terhadap Tenaga Medis yang Berkeadilan - Panji Asmara, Gregorius Yoga (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the regulatory framework for investigating criminal acts committed by medical personnel from a justice-based perspective, particularly under Law Number 17 of 2023 concerning Health. It also seeks to identify procedural weaknesses and their implications for the legal protection of medical professionals. Methodology: Using a normative legal approach, this research examines the 1945 Constitution, the Criminal Procedure Code, and Law No. 17 of 2023. Legal materials were obtained through literature review involving primary (laws and court decisions), secondary (academic books and journals), and tertiary sources (legal dictionaries). The data were analyzed through legal interpretation, comparison, and normative argumentation, focusing on professional ethics, institutional authority, and justice principles. Results/Findings: The study finds inconsistencies in how investigations involving medical personnel are regulated. The Medical Disciplinary Panel (MDP) is often misinterpreted as having investigative authority rather than acting as a professional advisor. Coordination gaps between medical and legal institutions weaken procedural fairness and protection. A more just framework requires clarity on institutional roles and the protection of both public interests and professionals’ rights. Conclusions: A fair investigation framework must redefine the MDP’s role, enhance inter-agency coordination, and ensure balanced mechanisms aligned with justice. Limitations: This research is limited to doctrinal legal analysis and does not incorporate empirical data or socio-cultural perspectives. Contributions: This study proposes a justice-oriented model for handling legal cases involving medical personnel, reinforcing legal certainty, institutional synergy, and the balance between ethical standards and criminal accountability.